Salt response in pepper (Capsicum annuum L.): components of photosynthesis inhibition, proline accumulation and K+/Na+ selectivity - Gammoudi, Najet; Ben Yahia, Leila; Lachiheb, Belgacem; Ferchichi, Ali (Journal of Aridland Agriculture, 2016)
Three salinity of irrigation water (control, 70, 120 and 170 mM NaCl) were applied to five cultivars of hot pepper (Capsicum annuum L.) collected from the South of Tunisia. After three weeks, relative water content, photosynthetic pigment levels, gas exchange, proline, soluble sugars and ions K+ and Na+ concentrations were measured. The results showed that the inhibition of photosynthesis was not mainly stomatal, but probably biochemical manifesting by a stability of stomatal conductance up to 120 mM NaCl and accompanied by a continuous increase in intercellular CO2 concentration under the three concentrations of salt. Proline content increased considerably as a result of stress and reaches almost double those of controls in cultivars Alaya, Shkira and Sgay and even triple in cultivars Maghraoua and Farch. Solubles sugars do not contribute effectively to the osmotic adjustment. Mineral analysis showed that until 120 mM NaCl, the highest concentration of Na+ was obtained in stems, probably reflecting the existence of a re-circulation mechanism of Na+. Meanwhile, salinity reduced the foliar K+ content. At stems level, K+ concentration does not show significantly disruptions compared to control. However, at the roots, there is a continuous increase in potassium content. For K+/Na+ shoot ratio and at 70 mM NaCl, all cultivars showed a decrease of selectivity except cv. Maghraoua. At 120 and 170 mM, the same cultivar showed the lowest reduction. In root system, at 70 mM NaCl, cv. Maghraoua showed the greater improvement of selectivity.Â 